Turmbau zu Babbeln… - Zielony, Katarzyna (Investigationes Linguisticae, 2011)
This article presents a general approach to language varieties from a non-native perspective. The following ideas were taken into consideration: Is research on dialects from a non-native point of view possible? What methods are recommended? Are dialects present in modern media and literature? If so, what does it mean for a translator? What is the role of mass media in the educational process of language acquisition? What do notions like: ‘society’, ‘nation’, and ‘integration’ have in common with language? These and other questions about language varieties and dialects have been the subject of consideration of a student dialect group established in 2009 at Adam Mickiewicz University in Poznań. The first results are partly reviewed in the article. The students want to deal further with the linguistic phenomena in terms of national identity and integration.